The genotype does not influence the establishment of elephantgrass (Pennisetum purpureum Schum.) - Robson Elpídio Pereira Ribeiro; Alexandre Carneiro Leão de Mello; Márcio Vieira da Cunha; Suellen Brandão de Miranda Costa; Janerson José Coelho; Rayanne Thalita de Almeida Souza; Mércia Virginia Ferreira dos Santos (Acta Scientiarum. Animal Sciences, 2022)
This study investigated whether genotype influences the establishment of Pennisetum purpureum Schumach. The experimental design was a randomized complete blocks with four treatments and eight replications (n=8). The treatments were four genotypes of P. purpureum, two classified as tall sizes: P. purpureum cv. Elephant B and cv. IRI 381; and two as dwarf types: P. purpureum cv. Mott and Taiwan A-146 2.37. They were planted in a tropical wet and dry region of Brazil. Tall genotypes showed superior field sprouting rates (p < 0.05), ranging between 95-99%, while dwarfs varied between 88-90%, however, Elephant B and IRI 381 produced a much lower average number of tillers (31 and 32 linear m-1, respectively), than Taiwan A-146 2.37 and Mott (56 and 41 linear m-1, respectively) (p < 0.05). Dwarf genotypes produced lower biomass yields (p < 0.05), but this was genotype-dependent and did not impact on their establishment. The levels of non-structural carbohydrates (NSC) (>10%) in the planted stems were associated with satisfactory field sprouting of the elephantgrass genotypes. Despite some variations between the genotypes in terms of sprouting, tillering, and growth rates, the kind of genotype had no major significance on the establishment of the elephantgrass.